Enhancement of Antibacterial Activity of Face Mask with Gold Nanoparticles - Khasro, Farah sadiq; Shuker Mahmood, Hanaa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
The emergence of new dangerous diseases worldwide has led to the need to think about the possibility of enhancing prevention by using new technologies. One of the most important requirements emphasized in the recent studies is the effectiveness of the masks against pathogenic bacteria. In this study, the efficiency of anti-infection protective face masks against bacteria was enhanced by using gold nanoparticles prepared by the chemical precipitation method. The absorption spectrum of the prepared gold suspension shows a clear plasmonic peak at 522 nm. The measurements showed that the sample was made of polypropylene fibers, where X-ray diffraction tests showed peaks matching its crystalline structure. Immersion with gold suspension led to the emergence of peaks belonging to the composition of gold. The immersion treatment increased Young's modulus from 36.5 to 61.7 Mpa. The antibacterial assay showed the efficacy of the samples against E-Coli bacteria with an inhibition zone of 3 cm.